A systematic review and meta-analysis on the impact of early vs. delayed pharmacological thromboprophylaxis in patients with traumatic brain injury - Muhammad Hamza Shuja (19748620) (2024)
Background Traumatic brain injury (TBI) poses significant health challenges, often leading to complications such as venous thromboembolism (VTE) and increased mortality rates. The administration of early post-traumatic prophylaxis (PTP) is intended to mitigate these risks and enhance overall patient recovery. This study aims to perform a systematic review and meta-analysis assessing clinical outcomes associated with early versus late pharmacologic thromboprophylaxis in TBI patients. Methods We conducted a literature search across PubMed and Scopus databases from their inception to March 2024. Data from eligible studies were aggregated using the generic inverse variance method, with outcomes reported as odds ratios (OR). Results The review encompassed 20 studies involving 87,726 patients. Early PTP was categorized based on the timing of administration: 1) within 24 h, 2) within 48 h, and 3) within 72 h of hospital admission. Our findings indicated that early prophylaxis significantly reduced the incidence of VTE, deep vein thrombosis (DVT), pulmonary embolism (PE), and overall mortality when compared to late administration. Specifically, early PTP was associated with a markedly lower risk of VTE (OR: 0.38; 95 % CI: 0.30 to 0.48; P < 0.00001), DVT (OR: 0.32; 95 % CI: 0.25 to 0.41; P < 0.00001), and PE (OR: 0.39; 95 % CI: 0.31 to 0.49; P < 0.00001). Furthermore, the analysis revealed a significant reduction in all-cause mortality within the early PTP group (OR: 0.71; 95 % CI: 0.53 to 0.97; P = 0.03). However, while statistically significant improvements were observed in the <48-hour subgroup, neither the <24-hour nor <72-hour groups achieved statistical significance. Conclusion These robust findings highlight the potential of early pharmacologic thromboprophylaxis as a crucial intervention to enhance patient outcomes following traumatic brain injuries. Other Information Published in: Journal of Clinical Neuroscience License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jocn.2024.110936